Mental health challenges and experiences in displaced populations following Hurricane Sandy and Hurricane Harvey: the need for more comprehensive interventions in temporary shelters. Issue 10 (29th April 2018) - Taioli, Emanuela; Tuminello, Stephanie; Lieberman-Cribbin, Wil; Bevilacqua, Kristin; Schneider, Samantha; Guzman, Maria; Kerath, Samantha; Schwartz, Rebecca M
Abstract : Hurricane exposure can have a profound impact on mental health, leading to increased symptoms of stress, anxiety, depression and post-traumatic stress disorder that are still present years after the storm. Those displaced following a hurricane are particularly vulnerable to adverse mental health outcomes, especially if displaced to temporary shelters. The current work highlights the experiences and mental health challenges of displaced populations following Hurricane Sandy and Hurricane Harvey, as well as describing barriers to conducting research in the immediate aftermath of Hurricane Harvey and the need for more comprehensive interventions in these vulnerable populations.